Evaluation of gastro protective effect and wound healing potential of cibotium barometz and vitex pubecsens in an animal model / Nahla Saeed Ibraheem Alwajeeh - Nahla Saeed , Ibraheem Alwajeeh (2017)
Cibotium barometz and Vitex pubescens are Malaysian medicinal plants used traditionally as remedies for gastrointestinal ailments and wounds. The present study aimed to assess the gastro protective effects and wound healing potential of both leaves of plants. In vitro, their ethanol extracts showed high antioxidant capacities with no cytotoxic effects on WRL-68 cell line. The active compounds identified were 24- Methylenecycloartanol in C. barometz and Vitexin with Luteoloside in V. pubescens. Down regulation of Bax and up regulation of Col1a2 genes were observed in Hs27 fibroblast cells treated with C. barometz. In vivo, neither hepatotoxicity nor nephrotoxicity was detected in the acute toxicity test of treated Sprague Dawley (SD) rats with each plant. In a dose-dependent manner, the rats pre-treated with each extract prior to being ethanol induced with gastric ulcers showed significant decreasing of ulcer area, moderate to mild disruption of the surface epithelium with reduction in submucosal oedema and leucocyte infiltration in the gastric tissue comparing to ulcer control group. Moreover, Periodic acid Schiff (PAS) stain demonstrated an increasing in glycoprotein content of gastric mucus barrier, over expression of Heat Shock Protein 70 (HSP70) and down-expression of Bcl-2-associated X protein (Bax) in rats pre-fed with each plant. Gastric tissue homogenates revealed significant increase of superoxide dismutase activity (SOD) and decrease of malondialdehyde (MDA) levels. In the wound healing studies, the normal wounds of each rat that dressed with C. barometz and V. pubescens leaves demonstrated a reducing of the wound closure area and acceleration of the wound healing potential in a dose independent manner and time of dressing. Moreover, the granulation tissues of wounds stained by hematoxylin and eosin (H&E) displayed the increases of fibroblast proliferations, vascularization, and collagen depositions with fewer inflammatory cells. In addition, Masson‟s trichrome (MT) staining of each dressed rat demonstrated high collagen accumulations and generations iv of new capillary vessels of the endothelial cells in the dressed rats when compared to carboxymethyl cellulose (CMC 2%) of vehicle group. The protein expressions of HSP70 was up regulated but Bax was down regulated were down regulated, elevated of SOD endogenous enzyme activities and dropped of MDA levels of normal skin wounds were exhibited in normal rats compared to the vehicle group. However, the results of diabetic wound had more time to be healed than normal wounds in the rats of experiments as a result of delaying in the chronic diseases. The diabetic wounds in rats, which dressed with C. barometz and V. pubescens leaves showed a lower of wound closure area and acceleration of the wound closure percentage of wounds in a dose independent manner and time of healing. Moreover, the granulation tissues of wounds using H&E staining exhibited the increases of fibroblast proliferations, vascularization, and collagen depositions with fewer inflammatory cells. Additionally, MT staining of treated rats demonstrated high collagen accumulations and generations of new capillary vessels of the endothelial cells in the dressed rats when compared to carboxymethyl cellulose (CMC 2%) of vehicle group. Conversely, the protein expressions of HSP70 was up regulated and Bax was down regulated of the skin tissue, elevated of SOD endogenous enzyme activities and dropped of MDA levels of diabetic rats were exhibited compared to the vehicle group. Therefore, the accelerated healing of wounds and ulcers in this study may be as a result of each plant in this study, which had antioxidant and anti-inflammatory properties particularly, C. barometz.